PELATIHAN PENGHITUNGAN NILAI PERSEDIAAN BARANG DENGAN METODE AVERAGE KEPADA SISWA-SISWI SMA HARAPAN JAYA - Rini Tri Hastuti; Muhammad Bintang Prajogi (PROSIDING SERINA, 2021)
From the preliminary survey, we found a problem where students at SMA Harapan Jaya had never been given knowledge about how to calculate inventory values using the average method. For this reason, I as a lecturer from the Faculty of Economics will provide a solution in the form of training on how to calculate inventory value using the average method to students at Harapan Jaya High School. The target that we want to achieve in this training is that after the training is held, the students at SMA Harapan will understand using the average method in assessing inventory. The implementation method that we will use in the training consists of several steps. First, conduct a preliminary survey by conducting interviews with the school. Second, prepare PPT training. Third, presenting PPT online with Zoom media. Fourth, we will give online quizzes to evaluate the extent of children's understanding of the material that has been explained. The outputs of this PKM activity are: Publications at Senapenmas or Serina and Pintar held by Tarumanagara University and POSTER at the Research Week event.